Sevelamer hydrochloride and coronary artery calcification in chronic hemodialysis patients: a new mechanism of action - Bahaa Eldin Zayed; Hussein El-Fishawy; Amal R Al-Shihaby; Mohamed A Salem; Usama A.A. Sharaf El Din; Mona Mansour (SpringerOpen, 2015)
Background The non-calcium-based phosphate binder sevelamer hydrochloride was developed to provide chronic kidney disease patients with a polymer capable of managing hyperphosphatemia without an increase in the calcium load. These beneficial effects were postulated as the mechanism of decreased progression of vascular calcification observed with such compounds. Our objective was to investigate the effect of low-dose sevelamer hydrochloride against calcium carbonate as phosphate binders on the coronary artery calcification score (CCS) and the fibroblast growth factor 23 (FGF23) level in patients receiving regular hemodialysis for more than 1 year, in a trial to find out a novel mechanism for the decreased vascular calcification observed during sevelamer use. Patients and methods A total of 80 hemodialysis patients were allocated into two groups each of 40 patients. The first group received sevelamer hydrochloride 2400 mg/day (group 1), whereas the second continued on calcium carbonate 1500 mg/day (group 2). For each patient, coronary artery calcification was estimated twice, once before admission to the study and again at the end of the study period using noncontrast computed tomography. Serum calcium, phosphorus, intact parathyroid hormone (PTH), lipids, and FGF23 were also assessed in these two situations. Results Beside the significant decrease in serum calcium and phosphorus levels after the use of sevelamer for 6 months, there was a significant decrease in levels of FGF23 and the rate of CCS progress in group 1. Serum levels of total and low-density lipoprotein cholesterol decreased significantly in group 1. The serum PTH level did not show a significant change in either group. CCS showed a significant positive correlation with FGF23, but there was no significant correlation with serum calcium, serum phosphorus, or serum PTH in both groups. Conclusion Sevelamer hydrochloride suppressed the progression of coronary artery calcification, and decreased the FGF23 level significantly. The significant correlation between the serum FGF23 level and the CCS in the absence of any significant correlation between the latter on the one hand and the serum calcium, the serum phosphorus, or the serum PTH on the other might highlight a novel mechanism of action of sevelamer on the CCS.